2018
DOI: 10.1016/j.jcrc.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effectiveness of noninvasive and invasive ventilation in patients with pneumonia

Abstract: Initial NIV was associated with better survival among the subgroup of patients hospitalized with pneumonia who had COPD or heart failure. Patients who failed NIV had high in-hospital mortality, emphasizing the importance of careful patient selection monitoring when managing severe pneumonia with NIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 40 publications
2
23
0
2
Order By: Relevance
“…We also explored the utility of NIV in patients with pneumonia. This has been controversial; prior studies have reported conflicting results, probably because of differences in clinical characteristics (pneumonia severity, age, or comorbidities) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In patients with pneumonia, the median PaO 2 /FiO 2 ratio and the median SOFA score at NIV commencement were 155 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…We also explored the utility of NIV in patients with pneumonia. This has been controversial; prior studies have reported conflicting results, probably because of differences in clinical characteristics (pneumonia severity, age, or comorbidities) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In patients with pneumonia, the median PaO 2 /FiO 2 ratio and the median SOFA score at NIV commencement were 155 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, chronic obstructive pulmonary disease (COPD) and congestive heart failure (CHF) are common comorbidities in VOP and known to benefit from NIV in acute respiratory failure (2,10,11), possibly even in patients with pneumonia (2).…”
Section: Vopmentioning
confidence: 99%
“…Another concern is that studies assessing NIV in patients with pneumonia have yielded varying results (2,5,28,32), suggesting that NIV could even be harmful if applied to patients with a higher burden of non-respiratory organ dysfunctions or too hypoxemic (3, 4). Our subgroup analyses assessing effect modification did not suggest this was the case.…”
Section: Relationship With the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“… 4 For instance, in a recent study NIV was associated with increased survival among the subgroup of patients hospitalized with pneumonia who had COPD or heart failure. 19 Although current guidelines do not recommend NIV among patients with CAP, patients with COPD and heart failure may nonetheless obtain benefit from early and careful use of NIV in the acute care setting. 12 …”
Section: Patient Selectionmentioning
confidence: 99%